Food microbiology - Adams, M. R.; Moss, M. O.; McClure, Peter J. (Royal Society of Chemistry, 2016)
"Maintaining its general structure and philosophy to encompass modern food microbiology, this new edition provides updated and revised individual chapters and uses new examples to illustrate incidents with particular attention being paid to images. Thorough and accessible, it is designed for students in the biological sciences, biotechnology and food science as well as a valuable resource for researchers, teachers and practicing food microbiologists."--Page 4 of cover